Correlation between Implant Surface Roughness and Implant Stability: A Systematic Review - Marta Romero-Serrano; Manuel-María; Mariano Herrero-Climent; Blanca Rios-Carrasco; Javier Gil-Mur (MDPI AG, 2024)
The aim of this study was to find in the literature data on the relationship between implant surface roughness and implant stability achieved, from the time of placement to three months afterward, to help us to know what type of surface roughness is more favorable to guarantee implant stability and osseointegration. A systematic review was conducted in accordance with the PRISMA 2020 (Preferred Reporting Items for Systematic Review and Meta-analysis) statement, and the protocol was registered on the Open Science Framework. The specific inclusion and exclusion criteria were selected using the PICOS framework. The databases Medline (PubMed), Scopus, the Web of Science and The Cochrane Library were searched up to October 2023. The selection of studies and data extraction were conducted by two independent reviewers. The review included a total of 11 studies. A total of 1331 dental implant placements were identified. Two of the eleven selected studies were on humans in vivo, eight were on animals in vivo, and one was on animals in vitro. A statistically significant correlation between surface roughness and implant stability as measured by resonance frequency analysis (RFA) was not identified in ten of the eleven selected studies. It appears that there is no correlation between primary stability and the degree of implant roughness. However, there appears to be a correlation between the roughness of the implant and the degree of osseointegration, as indicated by bone-implant contact values. This correlation is more closely related to secondary stability. The great methodological variability makes it difficult to compare data and draw conclusions, so it would be desirable to agree on a common methodology to help draw appropriate conclusions from published studies.